2018
DOI: 10.1186/s13054-018-1964-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inspiratory recruitment of atelectasis by automated lung sound analysis as compared to four-dimensional computed tomography in a porcine lung injury model

Abstract: Background: Cyclic recruitment and de-recruitment of atelectasis (c-R/D) is a contributor to ventilator-induced lung injury (VILI). Bedside detection of this dynamic process could improve ventilator management. This study investigated the potential of automated lung sound analysis to detect c-R/D as compared to four-dimensional computed tomography (4DCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Fully automatic quantification of structural lung disease, i.e. quantitative CT (QCT), has already been used as a feasible method for the evaluation of emphysema, airways disease, interstitial lung disease or atelectasis in large study population [11][12][13][14][15][16][17]. Many studies have shown laboratory parameters correlate with the degree of lung involvement in COVID-19 pneumonia using semi-quantitative or quantitative scoring, especially inflammation parameters such as Creactive protein, D-dimer, interleukin-6, blood count or blood gas analysis [10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Fully automatic quantification of structural lung disease, i.e. quantitative CT (QCT), has already been used as a feasible method for the evaluation of emphysema, airways disease, interstitial lung disease or atelectasis in large study population [11][12][13][14][15][16][17]. Many studies have shown laboratory parameters correlate with the degree of lung involvement in COVID-19 pneumonia using semi-quantitative or quantitative scoring, especially inflammation parameters such as Creactive protein, D-dimer, interleukin-6, blood count or blood gas analysis [10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Separately, 4DCT was used to determine optimal lung-protective ventilation ( 39 ). Finally, Boehme et al has used this mode in porcine models to quantify recruit and de-recruitment atelectasis, which contributes to ventilator-induced lung injury ( 40 , 41 ).…”
Section: Applications Of Functional Lung Imagingmentioning
confidence: 99%